LAW-BASED STATE AND THE RULE OF LAW IN UKRAINE: SEMANTIC FEATURES AND EVALUATION CRITERIA - Kvasha А.S. (Pressing Problems of Public Administration, 2016)
The issue of semantic features of interpreting the legal state doctrines and the rule of law in Ukraine andcountries of the Continental Europe has been considered, and analysis of the rule of law indices made.